THE INFLUENCE OF PRODUCT QUALITY AND PRICE PERCEPTION ON THE REPURCHASE OF AQUA IN JAKARTA MEDIATED BY BRAND IMAGE - Fransiskus, Charlie; Rakhman, Abdullah (AIBPM Publisher, 2023)
The emergence of various competitors with similar products is a challenge for Aqua. Currently, Aqua is the most well-known bottled water brand in Indonesia. This attracts the attention of the author, who wants to find out the influencing factors by looking at it from the perspective of brand image, product quality, and price perception, which will later influence repurchasing. The sampling technique uses the judgment sampling method by distributing 108 online questionnaires to consumers of Aqua products in Jakarta. In analyzing the data, the structural equation modeling method was used with the SmartPLS program. The results showed that product quality had no effect on brand image or repurchase. Price perception has a positive and significant effect on brand image. Price perception and brand image have a positive and significant effect on repurchase. Brand image cannot mediate the effect of product quality on repurchase, but brand image is able to mediate the effect of price perception on repurchase. The writer suggested that Aqua can clearly demonstrate the superiority of product quality, which can assist consumers in assessing products and distinguishing them from brands with similar products, and hoped Aqua will continue to maintain price compatibility with the quality and benefits provided.